2005
DOI: 10.1093/humrep/deh805
|View full text |Cite
|
Sign up to set email alerts
|

Cryoloop vitrification of rabbit oocytes

Abstract: The fastest cooling rate in combination with EG and DMSO as cryoprotectants had the fewest adverse effects on the spindle configuration of rabbit oocytes and embryo development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 33 publications
2
32
0
Order By: Relevance
“…Until now, vitrification has been adopted to cryopreserve embryos [3,4], oocytes [5][6][7][8][9] and ovarian tissue [10][11][12][13]. Kuwayama reported that vitrification, compared with slow cooling, resulted in high survival rates for all stages of embryo development [14].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, vitrification has been adopted to cryopreserve embryos [3,4], oocytes [5][6][7][8][9] and ovarian tissue [10][11][12][13]. Kuwayama reported that vitrification, compared with slow cooling, resulted in high survival rates for all stages of embryo development [14].…”
Section: Introductionmentioning
confidence: 99%
“…The evaporative cooling causes the nitrogen to partially solidify, thus creating a nitrogen slush. Samples immersed in nitrogen slush cool more rapidly because they come into contact with liquid nitrogen sooner than those immersed in normal liquid nitrogen (Cai et al, 2005). The Vit Master vitrification machine can provide a very high cooling rate (up to 135,000 • /min).…”
Section: Innovative Vitrification Devicesmentioning
confidence: 99%
“…An important advantage of the use of nylon loop over conventional vitrification procedures is that the open system lacks any thermo-insulation layer; this, coupled with the small volume (< 1 µl) of vitrification solution, results in both rapid and uniform heat exchange during cooling (Lane et al, 1999a, b;Reed et al, 2002;Cai et al, 2005;Sheehan et al, 2006;Mukaida and Takahashi, 2008). By decreasing the volume of the cryoprotective solution we are able to increase dramatically the freezing speed and decrease the toxicity and osmotic side effects of the CPA (Pogorelov et al, 2006;Katkov and Pogorelov, 2007;Pogorelov et al, 2007).…”
Section: Acta Veterinaria Hungarica 57 2009mentioning
confidence: 99%
“…Vitrification using the nylon loop/cryoloop was previously used to successfully vitrify human, hamster, mouse, bovine and horse embryos as well as human, horse and bovine oocytes Lane et al, 1999a, b;Oberstein et al, 2001;Reed et al, 2002;Hochi et al, 2004;Cai et al, 2005;Sheehan et al, 2006;Mukaida and Takahashi, 2008;Liebermann and Tucker, 2008). Lane et al (1999b) vitrified mouse and human blastocysts in a cryoprotective solution containing DMSO, EG, F and S with the cryoloop procedure and assessed subsequent development.…”
Section: Acta Veterinaria Hungarica 57 2009mentioning
confidence: 99%